1992
DOI: 10.1083/jcb.119.5.1129
|View full text |Cite
|
Sign up to set email alerts
|

Glycosome assembly in trypanosomes: variations in the acceptable degeneracy of a COOH-terminal microbody targeting signal.

Abstract: Abstract. Trypanosomes compartmentalize most of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
1
2

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 42 publications
3
66
1
2
Order By: Relevance
“…This and other kinetoplastids are distinguished from diverse eucaryotic cells by the presence of glycosomes, a microbody-like organelle containing glycolytic and glycerol metabolic enzymes (Opperdoes 1987, Michels 1989, Blattner et al 1992. Corresponding glycolytical isoenzymes were also found to be present in the cytoplasm of most protozoa studied so far.…”
mentioning
confidence: 96%
“…This and other kinetoplastids are distinguished from diverse eucaryotic cells by the presence of glycosomes, a microbody-like organelle containing glycolytic and glycerol metabolic enzymes (Opperdoes 1987, Michels 1989, Blattner et al 1992. Corresponding glycolytical isoenzymes were also found to be present in the cytoplasm of most protozoa studied so far.…”
mentioning
confidence: 96%
“…Morphologically, the glycosomes closely resemble the peroxisomes found in higher eukaryotes, although their enzyme contents differ significantly [2]. Recent studies indicated that the import of proteins into the glycosome depends on a conserved C-terminal tripeptide motif, analogous to the C-terminal serine-lysine-leucine (SKL) sequence responsible for peroxisomal targeting of firefly luciferase [3,4]. Subsequent investigations showed that the C-terminal tripeptide sequence requirements for glycosomal import are considerably more relaxed than those for import of proteins into mammalian peroxisomes .…”
Section: Introductionmentioning
confidence: 99%
“…Maximal import was seen with a construct bearing the first 18 amino acids of aldolase, joined to the CAT initiator methionine via a four amino acid bridge (SSGT) of the same sequence as that used in the thiolase constructs (pHD457). Import of this protein, with about 30%, was at a level similar to that observed using a minimal C-terminal tripeptide signal from trypanosomal phosphoglycerate kinase, -SSL [16]. Inclusion of either more (pAldE, pHD436, pHD456) or fewer aldolase residues (pHD438, pHD442) clearly diminished import.…”
Section: Function Of the Pts-2 In Glycosomal Targetingmentioning
confidence: 62%
“…The presence of PTS-1-type signals has previously been demonstrated on many glycosomal proteins, although the spectrum of tolerated amino acid substitutions appears to be rather enlarged in comparison to other 'higher' eukaryotes [15,16]. As trypanosomatids are evolutionarily the earliest-branching eukaryotes to contain microbodies [17], it is of considerable interest to determine to what extent the import apparatus is conserved.…”
Section: **Present Address: Deutsches Krebsforschungszentrum Immentioning
confidence: 99%
See 1 more Smart Citation